2002
DOI: 10.1046/j.1365-2044.2002.02696.x
|View full text |Cite
|
Sign up to set email alerts
|

The effect of a pre‐operative infusion of Ringer's solution on splanchnic perfusion in patients undergoing coronary artery bypass grafting

Abstract: SummarySurgical patients develop a fluid deficit during pre-operative starvation. This study examines the effects of pre-operative fluid administration on haemodynamic variables, oxygenation and splanchnic perfusion in patients undergoing elective coronary artery bypass grafting. Forty-eight patients were randomised to receive either a pre-operative crystalloid infusion (crystalloid group, n ¼ 24) or no infusion (control group, n ¼ 24). Patients in the crystalloid group received a continuous infusion of Ringer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
6
0

Year Published

2003
2003
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 28 publications
1
6
0
Order By: Relevance
“…In a randomised‐controlled trial, 24 patients undergoing coronary artery bypass grafting received a supplementary crystalloid infusion (1.5 ml/kg/h) pre‐operatively. In comparison with the control group, these patients had an improved pre‐operative hepatic bloodflow 17 . However, as in the present study, intraoperative cardiac function did not differ between the groups.…”
Section: Discussionsupporting
confidence: 44%
See 1 more Smart Citation
“…In a randomised‐controlled trial, 24 patients undergoing coronary artery bypass grafting received a supplementary crystalloid infusion (1.5 ml/kg/h) pre‐operatively. In comparison with the control group, these patients had an improved pre‐operative hepatic bloodflow 17 . However, as in the present study, intraoperative cardiac function did not differ between the groups.…”
Section: Discussionsupporting
confidence: 44%
“…Klein et al 17 showed an increased splanchnic perfusion in a randomised trial in cardiovascular surgery after pre‐operative administration of 1.5 ml/kg crystalloid solution. In another study, a relevant improvement of intraoperative cardiac stability and decreased post‐operative morbidity was demonstrated after pre‐operative fluid loading with 2000 ml saline solution 18…”
mentioning
confidence: 98%
“…Based on the premise that patients develop a considerable preoperative fluid deficit because of bowel preparation, fasting and intraoperative fluid loss via the gut in prolonged abdominal surgery, volume and infusion therapies have traditionally been ‘generous’, meaning that patients often received five or more liters of fluid intraoperatively. This concept is supported by randomized investigations focused on intestinal perfusion enhancement of the mucosa and increased splanchnic perfusion during cardiac surgery 39 . Elevated intraoperative fluid regimes have been associated with a reduced incidence of mucosal hypoperfusion and severe complications.…”
Section: Anesthesiological Aspects Of Fast‐track Rehabilitationmentioning
confidence: 97%
“…Although the administration of crystalloids may improve hepatosplanchnic perfusion in preoperative cardiac surgical patients (10,11), this seems not to be true for patients with other forms of circulatory failure (12). Moreover, the administration of crystalloid and colloid solutions based on saline can actually result in metabolic acidosis and impaired gastric mucosal perfusion (13).…”
mentioning
confidence: 97%